The Legendre’s Symbol Modulo p and Its Some Elementary Results - Jianghua Li; Yuan Zhang (Journal of Mathematics)
The main purpose of this article is using the elementary methods and the properties of the character sums to study the calculating problem of the number of the solutions for one kind congruence equation modulo p (an odd prime) and give some interesting identities and asymptotic formulas for it.